APPLICATION OF A REALISTIC MATHEMATICS LEARNING APPROACH TO IMPROVE STUDENTS' NUMERACY LITERACY ON DATA AND UNCERTAINTY CONTENT - Sri Imelda Edo; Emi Renoat (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research aims to increase the Numeracy literacy of Agribusiness and Fisheries students on data and uncertainty content through the application of the PMRI learning approach in the context of fisheries production at PPI Oeba Kupang. The research method used is the Classroom Action Research Method (PTK). This research was carried out in the fisheries and marine department of the Agribusiness and Fisheries study program. The research subjects consisted of all 55 semester 1 students of the 2023/2024 academic year of the AGP study program. Based on the results of data analysis, it was found that the application of the PMRI Learning approach in the context of fisheries production at PPI Oeba Kupang was able to improve student learning outcomes regarding data and uncertainty content where the percentage of students who passed the classical completion standard continued to increase, from 50.90% in cycle 1, 72.72% in the second cycle, and 92.72% in the third cycle. 82.72% of students are categorized as having very high learning outcomes, and 82.13% of students are in the very high activeness category.